Evaluation of Buccolingual Inclinations of Upper Right and Left First Molars Among Facial Patterns (Latakia University Journal -Medical Sciences Series, 2024)
Objective: This study aimed to compare the buccolingual inclination of right and left first molars in adults with different vertical facial types. Methods: Cone-beam computed tomography images of 66 adult patients [age, 18–40 years] with skeletal Class II division I maxillomandibular relationships were assigned to normodivergent (n = 22), hypodivergent (n = 22), and hyperdivergent groups (n = 22) according to angular sella-nasion/gonion-menton measurements. Buccolingual inclination of first molars were measured relative to the or-or line. Results: There were no statistically significant differences among the buccolingual inclinations of the first maxillary molars in the studied groups (p > 0.05). Conclusions: Buccolingual inclinations of maxillary right and left molars are similar in normodivergent, hyperdivergent and hypodivergent adults in each separately with Class II division 1 sagittal relationships.